2019
DOI: 10.3233/nre-192702
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems contribute to post-concussive symptoms in service members with a history of mild traumatic brain injury without posttraumatic stress disorder or major depressive disorder

Abstract: BACKGROUND: Many with a history of mild traumatic brain injury (TBI) experience sleep problems, which are also common symptoms of stress-related and mood disorders. OBJECTIVE: To determine if sleep problems contributed unique variance to post-concussive symptoms above and beyond symptoms of posttraumatic stress disorder/major depressive disorder (PTSD/MDD) after mild TBI. METHODS: 313 active duty service members with a history of mild TBI com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Insomnia symptoms prevalence was assessed by a number of questionnaire measures and, in one instance, according to medical records. Nine studies solely reported overall prevalence of poor sleep quality, sleep disturbance or other insomnia symptoms at one time point post-mTBI [52][53][54][55][56][57][58][59][60], with only two studies reporting prevalence of insomnia symptoms at different time points post-injury [61,62]. Prevalence of insomnia symptoms varied considerably from 10.0% to 96.0%.…”
Section: Prevalence Of Post-mtbi Insomnia/insomnia Symptoms Using Non...mentioning
confidence: 99%
“…Insomnia symptoms prevalence was assessed by a number of questionnaire measures and, in one instance, according to medical records. Nine studies solely reported overall prevalence of poor sleep quality, sleep disturbance or other insomnia symptoms at one time point post-mTBI [52][53][54][55][56][57][58][59][60], with only two studies reporting prevalence of insomnia symptoms at different time points post-injury [61,62]. Prevalence of insomnia symptoms varied considerably from 10.0% to 96.0%.…”
Section: Prevalence Of Post-mtbi Insomnia/insomnia Symptoms Using Non...mentioning
confidence: 99%
“…Weight loss could be associated with insufficient calories or nutrients required to effect recovery and could signal other concerns, such as depression or financial problems. Weight gain can be associated with lack of motivation to exercise [34], fatigue [35][36][37][38], insomnia [35,[39][40][41],…”
Section: General Healthmentioning
confidence: 99%
“…Likewise, sleep disruption may undermine these same neurophysiological processes and impede post-concussive recovery ( 18 , 20 ). Indeed, poor sleep quality is linked to more severe post-concussive symptoms across vestibular, sensory, behavioral, and cognitive domains ( 24 , 25 ). In turn, such post-concussive symptoms are a robust risk factor for participation restrictions among post-9/11 Veterans with TBI ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to examine whether post-concussive symptoms mediate the relationship between sleep problems and participation restrictions among post-9/11 Veterans with mTBI. There is theoretical and empirical support for relationships between: (1) sleep problems and post-concussive symptoms ( 24 , 25 ); and, (2) post-concussive symptoms and participation restrictions ( 8 , 9 ). Thus, we hypothesized that the relationship between sleep problems and participation restrictions would be mediated by post-concussive symptoms.…”
Section: Introductionmentioning
confidence: 99%